Power Sector Policy Note for the Kyrgyz Republic - World Bank (Washington, DC, 2014)
This power sector policy note analyzes the principal challenges in the power sector of the Kyrgyz Republic and identifies possible solutions for overcoming them. To inform the analysis, the note describes historical operational and financial performance of the power sector companies between 2007 and 2012, and projects performance until 2030. It also describes the legal, regulatory and institutional arrangements in the sector, and compares the arrangements in the Kyrgyz Republic to those in other countries' power sectors. The note relies on discussions with, and data provided by key stakeholders, including the power companies, the Ministry of Energy and Industry and the Regulatory Department under the Ministry of Energy and Industry. The analysis in the note is targeted to inform, and support for the on-going reform efforts of the Government of the Kyrgyz Republic in the power sector. In 2012, the Government approved the Power Sector Development Strategy outlining key medium-term reform objectives for the sector, and in 2013 it approved the action plan for reforming the power sector to operationalize the strategy. The engagement of the World Bank and other donors in the power sector aims to support the implementation of the action plan. The note substantiates the need for reforms through analysis and proposes solutions consistent with the strategy and action plan.